Inovasi Teknologi dalam Strategi Pembelajaran Pendidikan Agama Kristen untuk Meningkatkan Literasi Belajar Siswa (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
Technological innovation in Christian Religious Education learning strategies aims to improve students' learning literacy comprehensively. In an era of globalization and rapid technological advancement, Christian Religious Education is required to adapt to digital learning media to ensure relevance and effectiveness. The use of various technologies, such as interactive learning videos, educational applications, and e-learning platforms, increases student motivation and active engagement in understanding Christian values ​​and integrating faith with knowledge. Learning strategies using attractive digital technology, a hybrid learning model that combines face-to-face and bold learning, and improving teacher competency are key to the successful implementation of this innovation. The research method used is descriptive qualitative based on a literature review that examines relevant scientific literature, books, and documents on technological innovation in religious education and improving learning literacy. Content analysis was conducted by grouping data based on themes such as technology type, learning strategy, and its impact on student literacy. The research results show that the integration of technology in Christian Religious Education learning provides a significant opportunity to create a technologically savvy young generation that is both mature in faith and character, and able to face the challenges of the times with steadfastness.